Unique kinase catalytic mechanism of AceK with a single magnesium ion. - Quanjie Li; Jimin Zheng; Hongwei Tan; Xichen Li; Guangju Chen; Zongchao Jia (PLoS ONE, 2013)
Isocitrate dehydrogenase kinase/phosphatase (AceK) is the founding member of the protein phosphorylation system in prokaryotes. Based on the novel and unique structural characteristics of AceK recently uncovered, we sought to understand its kinase reaction mechanism, along with other features involved in the phosphotransfer process. Herein we report density functional theory QM calculations of the mechanism of the phosphotransfer reaction catalysed by AceK. The transition states located by the QM calculations indicate that the phosphorylation reaction, catalysed by AceK, follows a dissociative mechanism with Asp457 serving as the catalytic base to accept the proton delivered by the substrate. Our results also revealed that AceK prefers a single Mg(2+)-containing active site in the phosphotransfer reaction. The catalytic roles of conserved residues in the active site are discussed.